YOUTH “MILITARY AND PATRIOTIC” CLUBS IN THE TEMPORARY OCCUPIED TERRITORIES OF DONETSK AND LUHANSK REGIONS: CREATION AND FUNCTIONING FEATURES - PASHKOVA, Olha (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to reveal the specifics of the activity of youth “military and patriotic” clubs in the temporarily occupied territories of Donetsk and Luhansk regions. The methodology of the research. Due to the historical genetic method of research, it became possible, based on a complex of open sources, to reproduce events in their chronological sequence and analyze the main aspects of the military and patriotic clubs functioning, historical systemic – to consider their activities as part of the system of the military and patriotic education formed by the occupational administrations. Scientific Novelty. In the article there have been made an attempt to analyze the organizational and substantive aspects of the functioning of such clubs, which have been established since 2014 in the temporarily occupied territories of Donbas. Direct military training of minors (with the use of weapons and ammunition) was entrusted to the individuals, who took part in the illegal armed formations with the appropriate content: practical focus (conducting basic military training on a permanent basis, organizing mass events, competitions, military camps, etc.) and ideological work (in particular, forming the image of the enemy, exploiting historical narratives of World War II in a pro-Russian interpretation with reference to the present, etc.). Conclusions. The training of youth in similar organizations, including the holding of events on the territory of the Russian Federation, gives reason to believe that the Russian military political leadership tried, on the one hand, to form a new identity for the population of certain regions of Donbas, and on the other hand, to provide minors with specific knowledge, skills and abilities related to military. The combination of these goals was aimed at the future use local youth as a potential mobilization resource in case of a full-scale invasion on the territory of Ukraine. Key words: military patriotic education, militarization, military training, ideological work, youth, club, temporarily occupied territory, Ukraine, Donbas, Russian Federation.